Unhealthy Lifestyle and Gut Dysbiosis: A Better Understanding of the Effects of Poor Diet and Nicotine on the Intestinal Microbiome - Martinez, Jason E.; Kahana, Doron D.; Ghuman, Simran; Wilson, Haley P.; Wilson, Julian; Kim, Samuel C. J.; Lagishetty, Venu; Jacobs, Jonathan P.; Sinha-Hikim, Amiya P.; Friedman, Theodore C. (Frontiers in Endocrinology, 2021)
The study of the intestinal or gut microbiome is a newer field that is rapidly gaining attention. Bidirectional communication between gut microbes and the host can impact numerous biological systems regulating immunity and metabolism to either promote or negatively impact the host’s health. Habitual routines, dietary choices, socioeconomic status, education, host genetics, medical care and environmental factors can all contribute to the composition of an individual’s microbiome. A key environmental factor that may cause negative outcomes is the consumption of nicotine products. The effects of nicotine on the host can be exacerbated by poor dietary choices and together can impact the composition of the gut microbiota to promote the development of metabolic disease including non-alcoholic fatty liver disease. This review explores the contribution of nicotine, poor dietary choices and other unhealthy lifestyle factors to gut dysbiosis.